(untitled) (Estudios humanísticos. Geografía, historia y arte, 1988)
If we study plublic offences in the Roman World one of them estands out for its amplitude, graveness, and indetermination: the crimen maiestatis. This essay anlyses several acts that were considered as maiestas in the First Roman Empire, as well as the various methods of death sentence used. All this is mainly based on two latín writers TACITUS and SUETONIUS.